Holocene faulting on the Yugamine fault of the Atera fault zone, central Japan - Taniguchi, Kaoru; Kaneda, Heitaro; Sugito, Nobuhiko; Uchida, Chikara; Hirouchi, Daisuke; Hiramatsu, Takahiro; Yasue, Ken-ichi (Active Fault Research, 2007)
The Yugamine fault,10 km in length, is in the north-central part of the Atera fault zone. We studied Holocene activity of the Yugamine fault through a trenching survey. We excavated a trench across the scarplet on the L 1 terrace at Obayashi district. Some humic layers and fluvial gravels are exposed on the trench walls. The Yugamine fault has cut through these layers to form a linear depression on its NE side. From the structural evidence along the fault plane and angular unconformity, we recognize at least four faulting events in this trench.